Neuroprotective Effect of Inula racemosa on Chronic Stress-Aluminum Chloride Induced Memory Deficits - Venkanna Rao, Bhagya; Loganathan, Kanimozhi; Raju, Sushma; Vasudev, Ramya (Indian Journal of Pharmaceutical Education and Research, 2026)
Introduction: Alzheimer's Disease (AD) is characterized by cognitive impairment resulting from the accumulation of amyloid beta and tau plaques, reduced Brain-Derived Neurotrophic Factor (BDNF) expression, neuronal death, and brain inflammation. Chronic stress accelerates aging, while aluminum, a neurotoxin, is implicated in AD pathology. Objectives: This study aimed to assess the potential beneficial effects of Inula racemosa on cognitive deficits induced by chronic stress and aluminum chloride exposure. Materials and Methods: Rats were subjected to restraint stress (3 hr per day) and aluminum chloride (100 mg/kg) for 21 days. Following this, Inula racemosa (200 and 400 mg/kg) was administered for 14 days. Cognitive function was assessed through the sucrose preference test, forced swim test, Novel Object Recognition Test (NORT), and T-maze task. Biomarkers such as amyloid beta, Brain Derived Neurotrophic Factor (BDNF), and antioxidants Superoxide Dismutase (SOD), Malondialdehyde (MDA), Glutathione (GSH), and Catalase (CAT) were measured in the hippocampus and prefrontal cortex. Results: Chronic stress and aluminum chloride exposure led to decreased antioxidant levels, reduced BDNF expression, cognitive decline, increased amyloid beta plaques, and depressive-like behavior. Treatment with Inula racemosa mitigated these effects, improving cognition by restoring recognition memory in the NORT and spatial working memory in the T-maze task while also alleviating depressive behavior. Furthermore, it reduced oxidative stress, increased antioxidant levels in the hippocampus and prefrontal cortex, decreased amyloid beta plaque formation, and restored BDNF expression. Conclusion: Inula racemosa exhibited antioxidant and neuroprotective properties, offering protection against neurodegeneration. These findings underscore the potential of phytochemicals as neuroprotective agents.
Keywords: Aluminum Chloride; chronic Stress; Cognitive Impairment; Amyloid Beta; BDNF; Inula racemosa.